The Existence Of Women In Meeting The Family Economy: The Impact Of The Covid-19 Pandemic - Arif Ferdian (Zien Journals, 2021)
COVID-19 has caused some men's jobs to become obsolete, and the existence of women is now beginning to emerge as a result. Women's ability to boost household income through temporary work possibilities created by micro, small, and medium enterprises (MSMEs), online companies (OLEs), and day jobs has begun to develop. Problems develop when women perform employment that is primarily performed by men, particularly in the South Sulawesi region. Where is still rich in tradition, custom, and religious teachings. Some individuals find it difficult to accept women who work or who serve as the foundation of the family. As a result, women still have restricted options for finding work in the area. The researcher is interested in examining the role of women in the household economy following the Covid-19 pandemic, based on the issues listed above. This study is descriptive qualitative in nature, describing a phenomenon or event based on what occurred or was discovered in the field. Observation, literature study, and documentation study were all used in the data collection process. Study results show that to increase the number of women in society, empowerment must be increased. South Sulawesi women must go through several stages to exist, including the stage of forming a caring attitude to increase self-capacity, the stage of changing abilities, skills, and knowledge insights that play a role in the development and improvement of intellectual ability that leads to independence. Culture, on the other hand, is a roadblock in the way of women being self-sufficient. Because of this, women in South Sulawesi must be able to function in social, political, and technological spheres while also maintaining their independence. To remove the cultural barrier that prevents women from advancing in South Sulawesi.
Keywords: stage; Sulawesi; independence; Culture